Answer:
h(4 - n) = 11n - 37
General Formulas and Concepts:
Pre-Algebra
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Distributive Property
Algebra I
Explanation:
Step 1: Define
h(t) = 7 - 11t
h(4 - n) is t = 4 - n
Step 2: Evaluate
- Substitute in t [Function]: h(4 - n) = 7 - 11(4 - n)
- [Distributive Property] Distribute -11: h(4 - n) = 7 - 44 + 11n
- [Subtraction] Combine like terms: h(4 - n) = -37 + 11n
- Rewrite: h(4 - n) = 11n - 37